Limiting radiation damage for high‐brilliance biological solution scattering: practical experience at the EMBL P12 beamline PETRAIII. (3rd February 2015) - Jeffries, Cy M.; Graewert, Melissa A.; Svergun, Dmitri I.; Blanchet, Clément E.
<x xml:space="preserve">Abstract</x> Radiation damage is the general curse of structural biologists who use synchrotron small‐angle X‐ray scattering (SAXS) to investigate biological macromolecules in solution. The EMBL‐P12 biological SAXS beamline located at the PETRAIII storage ring (DESY, Hamburg, Germany) caters to an extensive user community who integrate SAXS into their diverse structural biology programs. The high brilliance of the beamline [5.1 × 1012 photons s−1, 10 keV, 500 (H) µm × 250 (V) µm beam size at the sample position], combined with automated sample handling and data acquisition protocols, enable the high‐throughput structural characterization of macromolecules in solution. However, considering the often‐significant resources users invest to prepare samples, it is crucial that simple and effective protocols are in place to limit the effects of radiation damage once it has been detected. Here various practical approaches are evaluated that users can implement to limit radiation damage at the P12 beamline to maximize the chances of collecting quality data from radiation sensitive samples.